Heterozygosity of p16 expression in an oral squamous cell carcinoma with associated loss of heterozygosity and copy number alterations. Issue 5 (14th December 2018) - Ambele, Melvin A.; Pepper, Michael S.; van Heerden, Marlene B.; van Heerden, Willie F. P.
Abstract: Background: Oral field cancerization describes a multifocal development process involving many cells at once in response to prolong exposure to carcinogens. This case demonstrated differential p16 expression in different sections of the same HPV negative tumor on the floor of mouth in a patient with history of prolonged smoking. Methods: Histological examination, presence of HPV infection and OncoScan analysis of DNA extracted from two well‐defined areas with different p16 expression profiles were performed. Results: Histological and immunochemical analysis revealed the presence of a dual architectural pattern squamous cell carcinoma with a p16 negative and a p16 positive component. OncoScan analysis showed genetic changes that define field cancerization of the p16 negative tumor as revealed by mosaicism in both loss of heterozygosity and copy number alterations in cancer‐associated genes located on 3p, 7p, 9p 11q, and 17p. Conclusion: These changes were indicative of field cancerization in response to tobacco exposure.